Deciduous premolars of Eocene Equidae and their phylogenetic significance. (17th February 2018) - Rose, Kenneth D.; Holbrook, Luke T.; Luckett, W. Patrick
Abstract: The deciduous premolars of early Eocene Equidae from North America, conventionally attributed to 'Hyracotherium', are described and compared, based primarily on a sample of >60 specimens from the early Eocene Willwood Formation of the Bighorn Basin, Wyoming. The sample represents six to nine species assigned to multiple genera by some other authors, but in the absence of diagnostic characters of the deciduous dentition, species assignments remain ambiguous for most specimens. Consequently it is not clear which generic names should be applied, and we employ the widespread name 'Hyracotherium' (acknowledging that the type species may not be an equid). We observed considerable variation in our sample, but most differences are minor and are largely inconsistent with respect to time or taxa, hindering attempts to characterise deciduous premolar anatomy of particular species. Comparisons were also made to Bridgerian Orohippus and Uintan Epihippus, to other early perissodactyls, and to non-perissodactyls that have been considered close to the origin of Perissodactyla (phenacodontid condylarths and Cambaytherium ). Based on these comparisons, we confirm Butler's observation that the deciduous premolars of equids show increasing molarization and lophodonty through the Eocene. However, our evidence suggests that there was little directed change through most of the Wasatchian until Wa-7.